Construction and validation of a job-demand-control-support scale to measure work stress - Patlán Pérez, Juana (2022)
Objectives: To design and build-up an instrument to measure work stress based on the Karasek’s job-demand-control- support (JDCS) as well as to estimate its psychometric properties. Methods: several steps were implemented; a) systematic review of the literature, b) to determine the factorial structure of the scale, c) to apply natural semantic networks to identify the psychological meaning of factors in the scale, d) contrast the literature results with the semantic networks, e) to elaborate a reagent bank, f) to validate the scale with 60 expert judges, g) integration of the scale, h) application of the scale to 619 workers. Results: the scale had adequate validity construct and reliability values (Alpha-Cronbach of 0.711 and 0.890, respectively). Work stress positively correlated with job demand and negatively with job control. A higher work stress index was found among workers who presented psychosomatic disorders. Conclusions: the scale is valid and reliable to evaluate work stress.